2020
DOI: 10.1186/s43045-019-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep duration and insomnia with menstrual symptoms among young women in Upper Egypt

Abstract: Background: Disturbed sleep and menstrual symptoms are prevalent health conditions with limited successful treatments. This study aimed to detect the association between sleep problems and menstrual symptoms among young women in Upper Egypt. In this cross-sectional study, 4122 young women aged 12 to 25 years and residing in Beni-Suef City were recruited using a multi-stage random method. The participants were interviewed for their premenstrual disorders, dysmenorrhea, average daily hours of sleep, and insomnia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…An Egyptian study investigated the relationship between sleep problems and menstrual symptoms, the participants were 4122 women aged 12-25 years residing in Beni-Suef city in Egypt who were interviewed for their menstrual and sleep abnormalities during the previous 6 months. The authors reported that women with insomnia reported higher rates of dysmenorrhea and premenstrual symptoms (30). In addition, a study of 579 females conducted in Philadelphia that was part of a large study that researched the relationship between sleep duration and bleeding, this study reported a significant association between short sleep duration and poor sleep quality with heavier menstrual bleeding (17).…”
Section: Resultsmentioning
confidence: 93%

Sleep and menstrual irregularities: A systematic review

Mohammad Radhi Al-Magableh,
Ghalia Mohammad Abu Mohsen,
Besan Jebrin Muzher
et al. 2023
World J. Adv. Res. Rev.
“…An Egyptian study investigated the relationship between sleep problems and menstrual symptoms, the participants were 4122 women aged 12-25 years residing in Beni-Suef city in Egypt who were interviewed for their menstrual and sleep abnormalities during the previous 6 months. The authors reported that women with insomnia reported higher rates of dysmenorrhea and premenstrual symptoms (30). In addition, a study of 579 females conducted in Philadelphia that was part of a large study that researched the relationship between sleep duration and bleeding, this study reported a significant association between short sleep duration and poor sleep quality with heavier menstrual bleeding (17).…”
Section: Resultsmentioning
confidence: 93%

Sleep and menstrual irregularities: A systematic review

Mohammad Radhi Al-Magableh,
Ghalia Mohammad Abu Mohsen,
Besan Jebrin Muzher
et al. 2023
World J. Adv. Res. Rev.
“…Other factors include the perturbed actions of several hormones such as estrogen, progesterone, prolactin, and growth hormones. 45 In addition, many theories have traditionally reported that insomnia results from dysmenorrhea. 38 46 47 48 …”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to altered melatonin secretion which in turn impacts several hormones such as progesterone, estrogen, growth hormone, and prolactin. These hormones not only control the reproductive tasks but also influence sleep and circadian rhythms [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%